Adherence to Diaphragm Use for Infection Prevention: A Prospective Study of Female Sex Workers in Kenya. (9th February 2010) - Bukusi, Elizabeth A.; Gallo, Maria F.; Sharma, Anjali; Njoroge, Betty; Jamieson, Denise J.; Nguti, Rosemary; Bell, April J.; Eschenbach, David A.
Abstract : Objective . To assess adherence to and acceptability of the diaphragm among 140 female sex workers in Kenya in a 6-month prospective study. Methods . At baseline and bimonthly visits, participants were interviewed on diaphragm knowledge, attitude, and practices. We used principal component analysis and logistic regression to identify predictors of consistent use. Results . At 50% of 386 bimonthly visits, women reported consistently using a diaphragm with all partners during the preceding 2 weeks. Consistent use was significantly higher at the 6-month than the 2-month visit. Women reported less covert use with "helping" (regular sex partners to whom she could go for help or support) than with "other" partners. Perceptions that diaphragms are easier to use than condoms and that their lack of coital interruption is important were associated with consistent diaphragm use with both partner types. Partner support of diaphragm use is correlated with consistent use with "helping" partners only while higher parity, consistent condom use, and perceived lack of need of condoms as a benefit of diaphragms were associated with consistent use with "other" partners. Conclusions . Diaphragm acceptance among female sex workers in Nairobi was high. Future studies should distinguish between partner types when evaluating diaphragm adherence.